KEBERADAAN BAKTERI Escherichia coli PADA AIR PENCUCI IKAN DI PASAR PINASUNGKULAN KAROMBASAN MANADO - Sauyai, Andris Z; Mewengkang, Hanny Welly; Timbowo, Semuel Marthen (Sam Ratulangi University, 2014)
Waterish a chemical compound that is essential for the survival of living beings on this earth. The function of water for life cannot be replaced by other compounds. Therefore, the provision of clean water and enough quality to be one of the critical success factors in the fishing industry. Water is an important medium in the washing solvent fish, because the fish washing can reduce to eliminate hazardous chemicals or microorganisma Water cleaning process is usually done disinfection. Disinfectants are used in the fishing industry is the provision of chemicals, such as chlorine. According Winarno (1993), chlorine has been proven only ideal disinfectant. When put in the water will have immediate effect destroy most microbes. Based on economic calculations, efficiency and ease of use, the use of chlorine is a common method. This study aims to determine the presence of coli forms and E. coli bacteria were isolated from the washing water, the test was conducted at the Laboratory of Microbiology of Fishery Products, Faculty of Fisheries and Marine Sciences, UNSRAT. Analysis Laboratory, the highest number of bacteria in the samples without making a second chlorine (A1): 4.5x103, and the lowest number of bacteria in samples containing chlorine taking second (A2): 3.3x102. In addressing the media that the EC Medium tubes positive coli form bacteria which produce acid and gas in the Durham tube. In order to show the EMB media E. coli growth are most numerous in the sample (A1), the washing water without containing chlorine.Keywords: Escherichia coli, clean water, washing water, chlorine.